Incidence and factors associated with early neonatal near miss in a tertiary care hospital in Bengaluru - Sunny, Sobin; Johnson, Avita Rose; Thimmaiah, Sulekha; Rao, P N Suman (Indian Journal of Child Health, 2020)
Background: Neonatal near miss is defined as, a neonate who has suffered a life-threatening condition but survived the first 28 days of life. As neonatal near miss is a predictor for early neonatal death, the lessons learned from near misses will be useful to help prevent early neonatal mortality. Objectives: The objectives of the study were to estimate the incidence of neonatal near miss and its associated factors in the early neonatal period in a tertiary hospital. Materials and Methods: This was a longitudinal study where all the cases of early neonatal near miss and early neonatal mortality were documented over a 1-year period. A face-validated structured questionnaire was used to collect information from mothers. The data were described using proportions, mean, and standard deviation. Regression analysis and adjusted odds ratio (aOR) were used to identify the determinants of early neonatal near miss. Results: The study was conducted among 210 neonates born to 197 mothers. The neonatal near miss rate in our study was found to be 75.43/1000 live births. The total live births during the study period were 2784. The most common cause of near miss was identified as birth weight of